Use of Plant Growth Promoting Bacteria in Banana: A New Insight for Sustainable Banana Production - Mia, Md. Abdul Baset; Shamsuddin, Zulkifli; Mahmood, Maziah (2010)
Banana, an important fruit crop, requires high amounts of chemical fertilizers for commercial cultivation, which is costly and can be hazardous to the environment, when used excessively. Plant growth promoting rhizobacteria (PGPR) could be used for growth promotion, nutrient uptake and some time as an alternative source of N-fertilizer of non-leguminous crops. Recently, research on PGPR for crop improvements are gaining prominence and thousands of research works have been published so far. However, use of this noble technique in banana production system is limited. Nevertheless, reports from various experimental findings suggested that PGPR strains could successfully formed colonies on the root surface of bananas, where more bacterial cells were found in the root hair proliferation zone. Application of PGPR alone could not produce significant benefits that require minimal or reduced levels of fertilizer-N consequently could produce a synergistic effect on root growth and development. The inoculation also increased the N yield and fixed N2 in association with banana roots subsequently increased the yield, improved the physical attributes of fruit quality and initiated early flowering. The summarized review suggested that PGPR are effective as a bioenhancer and biofertilizer for banana cultivation. For consistent and precise results extensive field experiments of bananas inoculated with PGPR strains should be continued.